2008
DOI: 10.1002/ima.20139
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback fMRI‐mediated learning and consolidation of regional brain activation during motor imagery

Abstract: We report the long-term effect of real-time functional MRI (rtfMRI) training on voluntary regulation of the level of activation from a hand motor area. During the performance of a motor imagery task of a right hand, blood-oxygenation-level-dependent (BOLD) signal originating from a primary motor area was presented back to the subject in real-time. Demographically matched individuals also received the same procedure without valid feedback information. Followed by the initial rtfMRI sessions, both groups underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 42 publications
(39 reference statements)
2
104
2
Order By: Relevance
“…This success rate is similar to that in a previous neurofeedback study where control over only one single visual ROI was trained (Scharnowski et al, 2012). Likewise, other neurofeedback studies have also reported that subsets of participants failed to learn self-regulation of brain activity (Bray et al, 2007;Chiew et al, 2012;deCharms et al, 2005;Johnson et al, 2012;Yoo et al, 2008). It is still one of the unresolved problems in neurofeedback and in brain-computer-interface (BCI) research, why a non-negligible number of participants (~20%) fail to learn control over the BCI ('BCI-illiteracy').…”
Section: Neurofeedback Learningsupporting
confidence: 84%
“…This success rate is similar to that in a previous neurofeedback study where control over only one single visual ROI was trained (Scharnowski et al, 2012). Likewise, other neurofeedback studies have also reported that subsets of participants failed to learn self-regulation of brain activity (Bray et al, 2007;Chiew et al, 2012;deCharms et al, 2005;Johnson et al, 2012;Yoo et al, 2008). It is still one of the unresolved problems in neurofeedback and in brain-computer-interface (BCI) research, why a non-negligible number of participants (~20%) fail to learn control over the BCI ('BCI-illiteracy').…”
Section: Neurofeedback Learningsupporting
confidence: 84%
“…Out of over 70 published rtfMRI-nf studies, very few reported that participants were unable to modulate brain hemodynamics (Berman, Horovitz, Venkataraman, & Hallett, 2011;Hampson et al, 2011). Other experiments using rtfMRI-nf, using sham-feedback as control, demonstrated that participants increased their ability to modulate a particular brain region throughout training Caria, Sitaram, Veit, Begliomini, & Birbaumer, 2010;Chiew, Laconte, & Graham, 2012;Hui et al, 2014;Lawrence et al, 2014;McCaig, Dixon, Keramatian, Liu, & Christoff, 2011;Rota et al, 2009;Rota, Handjaras, Sitaram, Birbaumer, & Dogil, 2011;Yoo, Lee, O'Leary, Panych, & Jolesz, 2008;Young et al, 2014;Zotev, Phillips, Young, Drevets, & Bodurka, 2013;Zotev et al, 2011). Many other studies often lacked necessary controls or appropriate analyses to determine that veritable neurofeedback was the primary factor accounting for the observed brain alterations (Thibault et al, 2015); Figure 2 depicts some common control conditions.…”
Section: Fmrimentioning
confidence: 99%
“…The spontaneous motor simulations of REM sleep may thus hold a special role even compared to waking motor imagery, which itself is increasingly recognized as a crucial component of the motor system, and a back door to enhancing motor performance after impairment, usually via task-designs (Abbruzzese et al, 1999, Bonnet et al, 1997, Decety, 1996, Fadiga et al, 1999, Jackson et al, 2001, Jeannerod, 1995, Jeannerod, 2001and Kober et al, 2014: Lehéricy et al, 2004, Porro et al, 1996and Schnitzler et al, 1997Sharma et al, 2006 andYoo et al, 2008). Note for example that motor control has been shown to be temporarily restored during REM sleep in Parkinson's patients who also exhibit REM sleep behaviour disorder (RBD;De Cock et al, 2007).…”
Section: Introductionmentioning
confidence: 99%